Automating Physical Database Design: Workload as a Sequence - Agrawal, Sanjay; Chu, Eric; Narasayya, Vivek (SIGMOD, 2006)
The area of automatic selection of physical database design to optimize the performance of a relational database system based on a workload of SQL queries and updates has gained prominence in recent years. Major database vendors have released automated physical database design tools with the goal of reducing the total cost of ownership. An important assumption underlying these tools is that the workload is a set of SQL statements. In this paper, we show that being able to treat the workload as a sequence, i.e., exploiting the ordering of statements can significantly broaden the usage of such tools. We present scenarios where exploiting sequence information in the workload is crucial for performance tuning. We also propose techniques for addressing the technical challenges arising from treating the workload as a sequence. We evaluate the effectiveness of our techniques through experiments on Microsoft SQL Server.